Monotonic optimization in communication and networking systems - Zhang, Ying Jun; Qian, Liping; Huang, Jianwei (Now Publishers, 2013)
Monotonic Optimization in Communication and Networking Systems provides a succinct and accessible introduction to monotonic optimization, including formulation skills and solution algorithms. Through several application examples, it illustrates modeling techniques and algorithm details of monotonic optimization in various scenarios
Keywords: Mathematical optimization